Past, Present and Future of Agroforestry Systems in Europe (Agroforestry - The Future of Global Land Use SE - 16, 2012)
Many traditional land-use systems in Europe involved agroforestry in the pre-industrial era, but, over the years, increased mechanization led to the develop- ment of increasingly specialized crop, animal and wood production systems. As a consequence, the area under agroforestry declined in many regions of Europe, and agroforestry systems became con fi ned to situations where understorey primary production is restricted due to cold temperatures (Boreal and Alpine areas) or drought (Mediterranean areas) and to plots that are hard to reach or too small for cultivation with modern machinery, as in Spain, Italy and the lower altitude mountain regions in southern and central Germany. On the whole, agroforestry continued to be practised only where it enabled farmers to obtain economic returns from lands that were otherwise relatively unproductive and mostly limited to silvopastoral practices. Since the mid-1990s, however, European policies have encouraged land management systems that combine production, environmental services (biodiversity, carbon sequestration, nutrient cycling and water quality) and social bene fi ts, and this has created a new interest in agroforestry systems. Today, the major agroforestry practices in Europe include silvopasture and silvoarable. However, the bene fi ts and opportunities offered by agroforestry can only be realized with substantial investments and coordinated efforts in research, education, knowledge transfer and appropriate national policies across Europe.

Soil nutrient status and forage yield at varying distances from trees in four dehesas in Extremadura, Spain (Silvopastoralism and Sustainable Land Management: Proceedings of an International Congress on Silvopastoralism and Sustainable Management Held in Lugo Spain, in April 2004, 2006)
The aim of this study was to understand the effect of holm-oak (Quercus ilex) on the soilnutrient concentration and its consequence on the yield of understory forage (Avena sativa) in four dehesas of CW-Spain. The soils of the dehesas varied in soil fertility (chromic Luvisols and Achrisols, and eutric Leptosols). Forage dry-matter yields were determined from 1-m2 sample plots at distances ranging from 2 to 20 m from the tree (9 trees per farm and year). Soil samples (0-30 cm depth) were also collected from the same sampling locations, and were analysed for pH, Electrical Conductivity, organic C, CEC, total-N, available N and base cations. Soil analysis results showed that the most of the values increased in the vicinity of the tree: organic C, total-N, CEC and exchangeable Ca2+ and K+. Differences in forage yield were mainly explained by fertilization dosage, light availability (estimated from Montero and Moreno, 2004) and soil CEC. In more fertile soils, forage production was negatively effected by the presence of the trees, as a consequence of light reduction (Competence), while in more oligotrophic soils, forage production was positively affetced by trees (Facilitation).